Microbiota in Human Periodontal Abscess Revealed by 16S rDNA Sequencing - Chen, Jiazhen; Wu, Xingwen; Zhu, Danting; Xu, Meng; Yu, Youcheng; Yu, Liying; Zhang, Wenhong (Frontiers in Microbiology, 2019)
Periodontal abscess is an oral infective disease caused by various kinds of bacteria. We aimed to characterize the microbiota composition of periodontal abscesses by metagenomic methods and compare it to that of the corresponding pocket and healthy gingival crevice to investigate the specific bacteria associated with this disease. Samples from abscess pus (AB), periodontal pocket coronally above the abscess (PO), and the gingival crevice of the periodontal healthy tooth were obtained from 20 periodontal abscess patients. Furthermore, healthy gingival crevice samples were obtained from 25 healthy individuals. Bacterial DNA was extracted and 16S rRNA gene fragments were sequenced to characterize the microbiota and determine taxonomic classification. The beta-diversity analysis results showed that the AB and PO groups had similar compositions. Porphyromonas gingivalis, Prevotella intermedia, and other Prevotella spp. were the predominant bacteria of human periodontal abscesses. The abundances of Filifactor alocis and Atopobium rimae were significantly higher in periodontal abscesses than in the periodontal pocket, suggesting their association with periodontal abscess formation. In conclusion, we characterized the microbiota in periodontal abscess and identified some species that are positively associated with this disease. This provides a better understanding of the components of periodontal abscesses, which will help facilitate the development of antibiotic therapy strategies.